2016
DOI: 10.1007/s00231-016-1932-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of melting and settling of an encapsulated PCM using variable viscosity

Abstract: demand and decrease pollution. This thermal energy can be stored and delivered back when needed.Latent heat thermal energy storage (LHTES) has become interesting to store thermal energy with a high storage density in a small temperature range. However, the low charging and discharging power of these units is due to the poor thermal conductivity of the phase change material (PCM) [2]. Macro-encapsulation of PCM may enhance the thermal distribution in thermal storage units by increasing the heat transfer area be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Correspondingly, A has the dimension m 2 for the cylindrical heat source (n = 1) or m for the rectangular heat source (n = 0). Nondimensionalizing the contact pressure (34) according to (14), and multiplying with a reference areaà = [n (π − 2) + 2] yields the non-dimensional contact forceF…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, A has the dimension m 2 for the cylindrical heat source (n = 1) or m for the rectangular heat source (n = 0). Nondimensionalizing the contact pressure (34) according to (14), and multiplying with a reference areaà = [n (π − 2) + 2] yields the non-dimensional contact forceF…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Due to its own weight the PCM tends to sink down to the bottom wall at which close-contact melting can be observed. This can be exploited to increase the rate of heat transfer into the storage and hence to optimize the charging time [14,10]. Other applications for close-contact melting are hot wire cutting manufacturing technology [18], nuclear technology [7,6], planetary protection [17] as well as robotic ice exploration technologies based on melting probes for polar research and solar system research, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Miehe [5] implemented and compared the viscosity and Darcy model to investigate the twin-roll casting process of the magnesium alloy. Kasibhatla et al [6] adopted the variable viscosity model to study the melting and settling of PCM in a capsule. More recently König-Haagen et al [7] performed a comprehensive benchmarking of fixed-grid methods and presented a qualitative and quantitative analysis of most common energy formulations for the modeling of melting.…”
Section: Introductionmentioning
confidence: 99%
“…Since specific heat is also held constant in these simulations, thermal diffusivity ∝ = k/(ρCp) varies predominately with thermal conductivity k (which is variable in the simulations) in both the physical experiments and the simulations. Second, while recent work that has shown that so-called close contact melting created by sinking solids within a PCM can lead to increases in melting rates [100,[121][122][123], the effects of close-contact melting are likely to be limited in this work. This is because the experiments depend on the use of 7-8 TCs within the salts, and these TCs would severely restrict the movement of a free-floating solid.…”
Section: Simulation Domainmentioning
confidence: 99%
“…This might affect the physical results both in the expansion and contraction of the overall volume of the salts within the chamber and also in the possibility that solid salts might become unattached to the side of the LHTSD and sink within the liquid. The latter concern is particularly notable considering recent work that has shown that so-called close contact melting created by sinking solids within a PCM can lead to large increases in melting rates [100,[121][122][123].…”
Section: Governing Equations and Discretization Schemementioning
confidence: 99%